2003
DOI: 10.1002/eat.10194
|View full text |Cite
|
Sign up to set email alerts
|

Ecologic momentary assessment of eating‐disordered behaviors

Abstract: These results suggest that EMA is a feasible and valid approach to the measurement of disordered eating behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 29 publications
8
101
0
Order By: Relevance
“…Second, it is unknown to what extent self-monitoring of affect, stress, and behavior influenced the participants, although we used a 2-day run-in period, and there were not gross trends in reporting levels of our primary constructs over time (a crude indicator that there were not strong reactivity effects). Also, previous EMA studies with BN participants have revealed minimal effects of reactivity (e.g., Stein & Corte, 2003). Third, this study focused on short-term antecedent A major strength of this study was the use of a substantial sample (n ϭ 131) of clinically diagnosed women with BN.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is unknown to what extent self-monitoring of affect, stress, and behavior influenced the participants, although we used a 2-day run-in period, and there were not gross trends in reporting levels of our primary constructs over time (a crude indicator that there were not strong reactivity effects). Also, previous EMA studies with BN participants have revealed minimal effects of reactivity (e.g., Stein & Corte, 2003). Third, this study focused on short-term antecedent A major strength of this study was the use of a substantial sample (n ϭ 131) of clinically diagnosed women with BN.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also questioned whether the self-monitoring accompanying daily diary designs may induce reactance (i.e., behavioral change occurring as a result of being assessed or monitored; Affleck, Zautra, Tennen, & Armeli, 1999). Although there is evidence suggesting that reactance is not problematic in diary studies of disordered eating (K. F. Stein & Corte, 2003), additional research is needed to better understand the possible role of reactance in daily diary designs. Another promising future direction is to use moderated mediation to test whether certain paths in the PMOBE differ for some individuals or change under particular conditions (Muller, Judd, & Yzerbyt, 2005).…”
Section: Present Limitations and Future Directionsmentioning
confidence: 99%
“…In most studies with pain disorder patients, higher pain ratings were found by retrospective assessment. 19,20 In eating disorders, a study with subthreshold bulimia and anorexia nervosa patients examined the concordance between EMA and the eating disorder examination (EDE), 18,21 the common clinical interview for assessing eating disorders. Again the results indicated that binge eating and excessive exercise over the time span of 28 days were lower when measured by EMA compared to the interview.…”
Section: Introductionmentioning
confidence: 99%